Improved Multi-secret Sharing Scheme Based on One-Way Function - Geng Yong-Jun; Guo Li-Zheng; Zheng Ming-Hui (Institute of Advanced Engineering and Science, 2014)
The weakness He-Dawson’s threshold multi-secret sharing scheme is presented and analyzed. By using the one-way function thought in the He-Dawson scheme, a new multi-use and multi-secret sharing scheme is proposed. The improved scheme is multi-time-use of once secret shares distribution and can resist conspiring attack. Furthermore, the new scheme is multi-secret sharing, group secrets can be reconstructed in free order and different group secret is corresponding to different threshold value which can meet with different practical application. At last, the security and efficiency of the new proposed multi-secret sharing scheme are analyzed. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5483